Economics - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
The long-term objective of the economics section of the Centro Internacional de Agricultura Tropical is to analyze the potential impact of improved cassava technology in Latin America. On-farm trials conducted in Media Luna (Magdalena) and Mondomo (Cauca) are described as well as cassava/maize intercropping trials. A case study analyzing the cassava market in the poultry industry in Colombia is included. Tables were also presented on yields and net incomes from various cassava and maize intercropping systems at Media Luna and cassava and bean intercropping systems at Caicedonia; DM and fiber content, and percentage of total roots with root rot of 4 cassava lines at different harvesting times; fresh root yield of var. Americana and Algodona on individual farms related to plot history and farm size at Mondomo. (CIAT)